Costs, Revenues, and Effectiveness of the Copenhagen Accord Emission Pledges for 2020 - Dellink, Rob (OECD Environment Working Papers, 2010)
Tackling the problem of global climate change requires a high level of international cooperation. Many countries have pledged targets or actions to reduce greenhouse gas emissions in the Appendices to the Copenhagen Accord. This analysis examines the costs and effectiveness of these pledges, using the OECD's ENV-Linkages computable general equilibrium model. Several scenarios are analysed to evaluate the impacts of the range of pledges, the use of offsets, and linking emission trading systems. The results show that while the emission targets currently pledged by a wide range of countries under the Accord are an important and welcome start to a global solution, the pledges are not ambitious enough to put us on a pathway to limit average global temperature increase to below 2°C. This paper also analyses the economic impacts of the pledges, and estimates the costs of action at around 0.3% of GDP for both Annex I and non- Annex I countries and 0.5-0.6% of global real income (not taking into consideration the economic benefits from avoided damages from climate change). Furthermore, the analysis reveals that the potential for increased fiscal revenue or proceeds are substantial and for the Annex I group of countries can exceed 1% of GDP (or 400 billion USD) if mitigation actions are achieved through market instruments such as carbon taxes or cap-and-trade emission schemes with auctioned emission allowances